Peran Partisipasi Karang Taruna Dalam Mendukung Pemilu Yang Demokratis dan Berkeadaban - Marratu Fahri; Ema Anita; Ella Puspita Sari; Harni Farhataini; Adam Purba; Okto Vianus (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Youth as agents of change can be realized in participating in participatory supervision of the democratization process. The importance of the strategic role of youth participation in accelerating development, including in the life of the nation and state. Incidentally, the Indonesian people are heterogeneous, making general elections the main means of democracy. This street vendor activity aims to increase community participation, especially youth at the village level in monitoring the upcoming general election. This activity took place in Tanjung Kemala Village, East Baturaja District, running smoothly. The results of this street vendor activity showed good results and were quite effective as a first step in providing a basic understanding regarding the stages of democratic elections for young people.